POLITISASI PESANTREN DAN PERGESERAN FUNGSI PESANTREN DI MADURA - Merlia Indah Prastiwi (Institut Agama Islam Negeri Madura, 2015)
Pesantren is an institution for learning, moral formation, and missionary endea-vor. In Madura, pesantren and kiai are essential elements that could not be separated from the life of the Madurese. Both have become the lifeblood of the Madurese. Being a kiai has its own image in Madura. A kiai is often considered a sacred figure who is always enlightening, who has words and behavior that deserves to be emulated. Inevitably, in Madura they have a lot of mass and followers, which in turn the realms of belief in kiai switch from that of the religious to political nuances in nature. This paper examines how the function of pesantren as a center for religious studies has shifted: from the role of pesantren which is religious nuances to that of more political nuances. From the sample of pesantren in Madura, precisely in three districts (Bangkalan, Pamekasan, and Sumenep) the study found various responses of the function shift of pesantren. In general, although there are some who question kiai involvement in the political sphere, the vast majority of the community supports kiai’s involvement in politics.This fact can be understood because Madurese still position kiai as a major figure and model, thus the involvement of kiai in politics is expected to change the negative image of politics.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i2.719